Erectile Dysfunction in Qatar: Prevalence and Risk Factors in 1, 052 Participants—A Pilot Study. Issue 2 (1st June 2014) - Al Naimi, Abdulla; Majzoub, Ahmad A.; Talib, Raidh A.; Canguven, Onder; Al Ansari, Abdulla
Abstract: Aim: The aim of this study is to investigate the prevalence of erectile dysfunction (ED) in Qatar and to determine the risk factors associated with it. Materials and Methods: This is a cross‐sectional survey study of men attending the outpatient department at Hamad Medical Corporation in Qatar between February 2012 and February 2013. The International Index of Erectile Function (IIEF)‐5 questionnaire was used for data collection. In addition to the IIEF‐5 score, each participant's medical history was taken, with special emphasis on risk factors for ED, including diabetes mellitus (DM), hypertension (HTN), dyslipidemia, coronary artery disease (CAD), and smoking habits, and on their body mass index. Results: One thousand fifty‐two participants were randomly selected to fill out the IIEF‐5 questionnaire. The participants' mean age (±SD) was 41.87 ± 13.24 years. Analysis of replies to the IIEF‐5 showed that ED was present in 573 out of 1, 052 participants (54.5%). Fifty‐six (5%) participants had severe ED, 61 (6%) had moderate ED, 173 (16%) had mild to moderate ED, and 283 (27%) had mild ED. Risk factors for ED that held statistical significance were age (odds ratio [OR] = 2.9, 95% confidence interval [CI] 2.1–4.1, P  < 0.001), DM (OR = 2.6, 95% CI 1.7–3.9, P  < 0.001), HTN (OR = 1.6, 95% CI 1.1–2.5, P  = 0.012), dyslipidemia (OR = 1.5, 95% CI 1.1–2.4, P  = 0.024), and CAD (OR = 3.2, 95% CI 1.3–7.5, P  = 0.009). Conclusion: We found that the prevalence rate of ED in Qatar is quite similar to the regional reported rates. Overall, we demonstrated that nearly more than half of our participants suffered from ED. Besides age, DM, HTN, CAD, and dyslipidemia were found to be the most important risk factors for ED.